Workers Compensation Program Improvements: Managing Workplace Safety and Costs - Sheehan, Elijah; Reif, Kathryn; Gibert, Jocelyn; DeCramer, Carissa (My University, 2008)
The City of Milwaukee would like to identify management practices to increase workplace safety and reduce Workers Compensation costs. The authors identify promising practices in six comparable municipalities and evaluated these practices based on these performance management criteria: accountability, communication flow, incentives, benchmarks, and innovations.
For PA 869: Public Affairs Workshop, Domestic Issues